Nutrient transport by overland sheet flow on sites containing swine slurry - John E. Gilley (International Soil and Water Conservation Research)
Nutrients in agricultural runoff may cause offsite environmental impacts. The objective of this investigation was to examine nutrient transport by overland sheet flow on sites containing swine slurry. Data examined in this study was collected during field rainfall simulation tests conducted on cropland sites in southeast Nebraska, USA. Inflow was added to the top of experimental plots in four successive increments to simulate runoff rates occurring at greater downslope distances. Runoff rates on the experimental sites ranged from 2.3 to 21.2 L min−1 and maximum equivalent downslope distances varied from 5 to 108 m. Phosphorus (P) and nitrogen (N) transport rates were found to increase in a linear fashion with runoff rate. Hypothesis testing using the student’s t-test affirmed the prediction that a linear equation, calibrated for site specific conditions, can be used to relate nutrient transport rates to runoff rates. P and N transport rates were thought to be influenced by (a) the quantity of nutrients released by swine slurry at a particular runoff rate and (b) the amount of overland sheet flow available to transport the released nutrients. If nutrient transport rates can be linked to runoff rates, it may be possible to extrapolate experimental results obtained from small plots to greater downslope distances. Existing process-based models used to route overland sheet flow along hillslopes on upland areas could also be modified to include nutrient constituents.